PELATIHAN TECHNOPRENEURSHIP DI ERA DIGITAL UNTUK SISWA SMK SANTO LEO JAKARTA BARAT - Sutrisno Sutrisno (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2022)
SMK Santo Leo is a private school located in West Jakarta. Along with the times that are always developing, students' skills are required to be even better in order to compete after they graduate from school. One of them is the provision of Technopreneurship, namely the use and incorporation of technology to run a business or business because students must be motivated to become entrepreneurs after they graduate from school, especially in the era of the COVID-19 pandemic, almost all businesses are already using information technology. E-commerce applications are technologies that are used to combine technology and business. Santo Leo Vocational School is a school with expertise programs that have not yet been optimal in developing Technopreneurship technology for students, therefore holding community service is very appropriate to provide additional training and motivation to students. Currently, the method of providing students with expertise only uses the conventional method, namely jumping into the field, even though it can also be done using a more modern method. Technopreneurship has many advantages because it uses internet media so that its reach is wider. The goal is for students to be literate with technology that can be implemented in business. The benefit of the activity is to provide students with learning so that it can be used to create businesses that incorporate technology. The results to be achieved in this Technopreneurship training and development are the skills that students have so that they can develop more so that the technology used can be more effective and efficient in running a business or business.